New and recurrent X-ray transients in M31 observed with XMM-Newton in January 2016 - part 2 - Henze, M.; Sasaki, M.; Haberl, F.; Williams, B. F.; Hatzidimitriou, D. (The Astronomer's Telegram, 2016)
Here we report the second set of new and recurrent X-ray transients found in two XMM-Newton 100-ks pointings of the M31 northern disk on Jan 1 and 21 (see ATels #8825, #8826).
Keywords: Transient